2022
DOI: 10.1080/21655979.2022.2066748
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 protects against diabetic cardiomyopathy in the streptozotocin-induced diabetic mouse model via the p38-MAPK pathway

Abstract: Nesfatin-1 is a novel anorexigenic peptide that possesses antihyperglycemic and cardiovascular effects. We hypothesized that nesfatin-1 has a beneficial protective effect against diabetic cardiomyopathy (DC). We investigated the therapeutic effect of nesfatin-1 on diabetes-associated cardiac dysfunction in the high-fat diet (HFD)/streptozotocin (STZ)-induced diabetic mouse model. We found that the cardiac nesfatin-1 level was lower in diabetic mice than in normal mice. Nesfatin-1 treatment (180 mg/kg/day for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…[ 27 ] A study of Fan et al showed that treatment of streptozotocin and high fat diet (STZ‐HFD)‐induced diabetic rats with nesfatin‐1 attenuate cardiomyopathy by downregulating the p38 MAPK signaling pathway and associated cardiac apoptosis, fibrosis, inflammation, and oxidative stress. [ 28 ] A similar effect was observed in STZ‐induced diabetic mice where treatment with ivabradine exhibited cardioprotective effect by downregulating cardio‐specific p38 MAPK/JNK signaling and mediated inflammation, apoptosis, and oxidative stress. [ 29 ]…”
Section: Involvement Of Various Cellular Pathways In Dcmmentioning
confidence: 70%
“…[ 27 ] A study of Fan et al showed that treatment of streptozotocin and high fat diet (STZ‐HFD)‐induced diabetic rats with nesfatin‐1 attenuate cardiomyopathy by downregulating the p38 MAPK signaling pathway and associated cardiac apoptosis, fibrosis, inflammation, and oxidative stress. [ 28 ] A similar effect was observed in STZ‐induced diabetic mice where treatment with ivabradine exhibited cardioprotective effect by downregulating cardio‐specific p38 MAPK/JNK signaling and mediated inflammation, apoptosis, and oxidative stress. [ 29 ]…”
Section: Involvement Of Various Cellular Pathways In Dcmmentioning
confidence: 70%
“…It is demonstrated that nicorandil, which activates the phosphatidylinositol‐3‐kinase (PI3K)/protein kinase B (PKB) pathway, reduces cardiomyocyte apoptosis and improves the symptoms of cardiac insufficiency in DM rats 84 . Moreover, studies have shown that Nesfatin‐1 improves insulin sensitivity in STZ‐induced DM model rats through the p38‐MAPK pathway, reducing inflammation and ameliorating cardiac dysfunction 85 …”
Section: Recent Advances In Treatment Researchmentioning
confidence: 99%
“…84 Moreover, studies have shown that Nesfatin-1 improves insulin sensitivity in STZ-induced DM model rats through the p38-MAPK pathway, reducing inflammation and ameliorating cardiac dysfunction. 85 In recent years, extensive research has shown that certain herbal extracts have potential therapeutic effects on DCM. [86][87][88][89][90][91] For instance, Schisandrin B has been found to alleviate DCM by targeting MyD88 and inhibiting MyD88-dependent inflammation.…”
Section: Other Medications or Potential Active Ingredientsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that nesfatin increases insulin sensitivity and has anti-inflammatory as well as cardioprotective effects. Thus, studies have shown that nesfatin inhibits MAPK signaling pathways, including p38 MAPK/c-Jun and IKK/NF-κB, and also reduces the levels of inflammatory cytokines IL-6, IL-1β, and TNF-α [ 120 , 121 , 122 ]. In addition, it has been found that nesfatin affects indicators of oxidative stress, namely, it suppresses the increased production of ROS, and also increases the activity of superoxide dismutase [ 122 ].…”
Section: Anti-inflammatory Adipokines In Obesity and Its Complicationsmentioning
confidence: 99%